Retinoic Acid Receptor β: A Potential Therapeutic Target in Retinoic Acid Treatment of Endometrial Cancer. Issue 4 (1st May 2017) - Tsuji, Keita; Utsunomiya, Hiroki; Miki, Yasuhiro; Hanihara, Mayu; Fue, Misaki; Takagi, Kiyoshi; Nishimoto, Mitsuo; Suzuki, Fumihiko; Yaegashi, Nobuo; Suzuki, Takashi; Ito, Kiyoshi
Abstract : Objective: Several studies have reported that retinoic acid (RA) might be used to treat malignancies. The effects of RA are mediated by the RA receptor (RAR), and RARα/RARβ especially acts as a tumor suppressor. However, little is known about its role in human endometrial cancer. Materials and Methods: In this study, we examined the effects of all-trans RA (ATRA) on progression of human endometrial cancer cell line, RL95-2 and Hec1A. We then examined the expression of RARα and RARβ in 50 endometrial cancer tissues by using immunohistochemistry. Results: We found inhibitory effects of ATRA on cell proliferation, apoptosis, and migration in RL95-2 cells, but not in Hec1A cells. RARα or RARβ knockdown individually could not cancel out the inhibition of cell proliferation by ATRA in RL95-2 cells, but simultaneous knockdown of RARα and RARβ could block its effect on proliferation. RARα and RARβ knockdown dose dependently reduced the inhibition of migration by ATRA, but the effect was more pronounced with RARβ knockdown than with RARα knockdown. We confirmed that RARβ gene was directly regulated by ATRA in microarray and real-time reverse transcription polymerase chain reaction. Furthermore, the RARβ agonist (BMS453) significantly suppressed proliferation of RL95-2 cells. In immunohistochemical analysis, RARα expression was positively correlated with tumor grade, and RARβ showed the opposite tendency in endometrial cancer. Conclusions: Retinoic acid might have multiple antitumor effects, and RARβ may be a potent therapeutic target in RA treatment for endometrial cancers.